Metal-directed assembly of two one-dimensional coordination polymers: Structural, theoretical, fluorescent and non-linear optical studies. (26th February 2016) - Zhao, Huajian; Jia, Ding; Meng, Suci; Li, Jianghua; Zhang, Chi
Graphical abstract: Two 1-D azo-containing bipyridyl-based Zn(II)/Cd(II) CPs1 and2 have been successfully constructed and characterized. Time-dependent density functional theory (TD-DFT) calculations of 4, 4′-azpy and1, together with the fluorescent and non-linear optical properties of1 and2 have also been investigated. Highlights: Two 1-D Zn(II)/Cd(II) coordination polymers were synthesized. The absorption spectra of 4, 4′-azpy and1 were calculated. The fluorescence and non-linear optical properties of CPs1 and2 have been investigated. Abstract: The reaction of Zn(II)/Cd(II) salts with azo-containing bipyridyl ligands afforded two coordination polymers (CPs), [Zn( μ 2 -4, 4′-azpy)(NO2 )2 ] n (1 ) and [Cd2 ( μ 2 -4, 4′-azpy)3 (NO2 )4 ] n (2 ) (4, 4′-azpy = 4, 4′-azopyridine). The identities of the CPs1 and2 have been unambiguously established by single-crystal X-ray diffraction, and further characterized by elemental analysis, powder X-ray diffraction, thermogravimetric analyses, electrospray ionization-mass spectrometry (ESI-MS), fluorescence analysis, Fourier-transform infrared and ultraviolet/visible spectroscopies. CP1 exhibits one-dimensional (1-D) zigzag chains containing an octahedral [ZnO4 N2 ] unit bridged by N-donor ligands in the crystal lattice. CP2 presents a 1-D ladder chain constructed by T-shape units of [Cd(NO2 )2 ( μ 2 -4, 4′-azpy)3 ] and further forms a 1-D → three-dimensional (3-D) interpenetrated structure. In addition, density functional theory and time-dependent density functional theory calculations at the B3LYP/LanL2DZf+6-31G ∗ level were performed on 4, 4′-azpy and CP1 to rationalize their experimental absorption spectra. The fluorescent properties of the free 4, 4′-azpy ligand, 1 and2 have been studied at room temperature. The results reveal that CPs1 and2 exhibit enhanced fluorescent emissions at about 410 and 427 nm compared with the 4, 4′-azpy ligand, respectively. Third-order non-linear optical (NLO) properties of1 and2 were also investigated.